Does Tourniquet Time in Primary Total Knee Arthroplasty Influence Clinical Recovery? - Rathod, Parthiv; Deshmukh, Ajit; Robinson, Jonathan; Greiz, Michelle; Ranawat, Amar; Rodriguez, Jose (The Journal of Knee Surgery, 2015)
There are limited data on the influence of a reduced tourniquet time strategy on the clinical outcome of primary total knee arthroplasty (TKA). The aim of our study was to prospectively compare clinical recovery in two groups of patients undergoing TKA based on differences in tourniquet strategy at the same institution. Group A (40 patients) consisted of TKAs performed by a surgeon using tourniquet from incision to arthrotomy closure, and group B (40 patients) consisted of TKAs performed by another surgeon using tourniquet only during cementation. The surgical technique, implants, perioperative management, and patient demographics were similar between groups. Average tourniquet time was significantly higher in group A (71.7 minutes) as compared with group B (36.8 minutes). The maximum hemoglobin (Hb)/hematocrit (Hct) drop was statistically higher in group B (Hb drop = 3.5 ± 0.9 g/dL; Hct drop = 11 ± 3) as compared with group A (Hb drop = 2.9 ± 0.9 g/dL; Hct drop = 9 ± 2; Hb drop p = 0.01; Hct drop p = 0.002). There were no significant differences in visual analogue scale pain scores, narcotic consumption, ability to straight leg raise during hospital stay, range of motion (ROM) at discharge, as well as isometric quadriceps strength, ROM, Short Form 36 scores, Knee Society scores at 6 weeks, 3 months, and 1 year follow-up with a similar multimodal pain management protocol. Radiographic analysis revealed no differences in cement penetration around the tibial component in any zone. Four patients developed pulmonary embolism (three in group A, one in group B) and five patients underwent manipulation under anesthesia for stiffness (four in group A, one in group B). Thus, the use of a tourniquet only during cementing in TKA increases the hemoglobin drop and does not significantly influence pain or clinical recovery with available numbers, but was associated with a lower incidence of early complications. It is a learned surgical skill which significantly reduces tourniquet time and achieves a similar quality of cementing.
Keywords: tourniquet time; primary; total knee arthroplasty